1, 4-Azaborine based unfused non-fullerene acceptors for organic solar cells. Issue 7 (31st January 2023) - Chen, Shihao; Dong, Minghao; Bai, Yuanqing; Chen, Yuting; Fu, Yuang; Shao, Lin; Lu, Xinhui; Liu, Chunchen; Zhang, Kai; Wu, Hongbin; Huang, Fei
Abstract : Two novel unfused acceptors, ABBT-BO(DT), featuring 1, 4-azaborine have been synthesized. ABBT-BO based OSCs achieved an optimal PCE of over 10% for higher exciton dissociation, improved carrier transport and suppressed charge recombination. Abstract : 1, 4-Azaborine, containing both boron and nitrogen in an aromatic hydrocarbon, displays unique electronic properties compared with its all-carbon analogue and shows great potential as a multiresonant thermally activated delayed fluorescence material. However, conjugated molecules featuring 1, 4-azaborine for organic solar cells (OSCs) have not yet been explored. In this study, two novel acceptor–donor–acceptor (A–D–A) conjugated molecules, ABBT-BO and ABBT-DT, using dithieno-1, 4-azaborine as the core D unit have been designed and synthesized. Both molecules exhibited excellent solubility, strong and broad absorption and appropriate energy levels, enabling them to be promising candidates for non-fullerene acceptors (NFAs). It was found that the shorter alkyl chain of ABBT-BO could endow the device with superior morphology, resulting in more sufficient exciton dissociation, improved carrier transport and suppressed charge recombination. Impressively, PM6 :ABBT-BO based OSCs achieved a power conversion efficiency (PCE) of 10.07% with an open-circuit voltage ( V OC ) of 0.900 V, a short-circuit current density ( J SC ) of 16.41 mA cm −2, and a fill factor (FF) of 68.16%, which is the highest efficiency reported for NFAs featuring BN-heteroarenes. This work demonstrates the significant potential of 1, 4-BN-heteroarenes for constructing novel NFAs toward high-performance OSCs.